2017
DOI: 10.1039/c6cp08110j
|View full text |Cite
|
Sign up to set email alerts
|

Infrared characterisation of acetonitrile and propionitrile aerosols under Titan's atmospheric conditions

Abstract: Pure, crystalline acetonitrile (CHCN) and propionitrile (CHCHCN) particles were formed in a collisional cooling cell allowing for infrared (IR) signatures to be compiled from 50 to 5000 cm. The cell temperature and pressure conditions were controlled to simulate Titan's lower atmosphere (80-130 K and 1-100 mbar), allowing for the comparison of laboratory data to the spectra obtained from the Cassini-Huygens mission. The far-IR features confirmed the morphology of CHCN aerosols as the metastable β-phase (monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“…While a metastable b-phase (monoclinic) ice was identified for CH 3 CN, there was no such phase observed for C 2 H 5 CN. Ennis et al (2017) also reported the 200-250 cm −1 region was absent of an CH 3 CN spectral feature, but found the ν 13 band of crystalline C 2 H 5 CN ice at 110 K was located at 226 cm −1 , which is in agreement with Dello Russo and Khanna (1996).…”
Section: Titan Stratospheric Ice Experimental Effortssupporting
confidence: 73%
See 2 more Smart Citations
“…While a metastable b-phase (monoclinic) ice was identified for CH 3 CN, there was no such phase observed for C 2 H 5 CN. Ennis et al (2017) also reported the 200-250 cm −1 region was absent of an CH 3 CN spectral feature, but found the ν 13 band of crystalline C 2 H 5 CN ice at 110 K was located at 226 cm −1 , which is in agreement with Dello Russo and Khanna (1996).…”
Section: Titan Stratospheric Ice Experimental Effortssupporting
confidence: 73%
“…Purifying the sample becomes very crucial, and unfortunately, most of the published laboratory work focused on Titan's stratospheric ices are impure. For example, some work efforts report CO 2 impurity bands in the infrared spectra of their synthesized ices, e.g., in the HC 3 N spectra reported in Moore et al (2010), in the C 4 N 2 ice spectrum of Khanna et al (1987), and in the CH 3 CN ice spectrum of Ennis et al (2017). This latter work effort also noted the cryopump oil impurities in their samples.…”
Section: Titan Stratospheric Ice Experimental Effortsmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Anderson et al 8 review the arguments for and against the presence of an essentially separate aerosol layer of cyanoacetylene ice in Titan's atmosphere. Very recently Ennis et al, 9 made laboratory IR spectra of pure ACN ice for comparison with Cassini data. While the match was poor, the authors note that one cannot distinguish between phases comprised of a mix of ACN with other species versus tiny grains of segregated pure ice.…”
Section: Introductionmentioning
confidence: 99%
“…8 The optical properties of a material can be inferred from experimental spectra from X-ray frequencies through to the Far-Infrared/Terahertz regions, in either transmittance or absorbance or reflectance mode. 2,[9][10][11][12][13] From the measured spectra, it is possible to extract both the real and imaginary components of the complex optical constants by employing the Kramer-Kronig (K-K) relation, a mathematical expression that connects the real and imaginary parts. 14 However, due to the limited range of available spectral data, the optical constants extracted by direct K-K analysis contain truncation errors.…”
Section: Introductionmentioning
confidence: 99%